2008
DOI: 10.1681/asn.2007111164
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oral Calcitriol with Improved Survival in Nondialyzed CKD

Abstract: Parenteral vitamin D is associated with improved survival among long-term hemodialysis patients. Among nondialyzed patients with chronic kidney disease (CKD), oral activated vitamin D reduces parathyroid hormone levels, but the impact on clinical outcomes is unknown. We evaluated associations of oral calcitriol use with mortality and dialysis dependence in 1418 nondialysis patients with CKD and hyperparathyroidism in the Veterans' Affairs Consumer Health Information and Performance Sets database. Incident calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
140
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(155 citation statements)
references
References 30 publications
10
140
1
4
Order By: Relevance
“…On the basis of observational and preclinical data, hypotheses have been generated that hyperphosphatemia, hypercalcemia, and calcitriol deficiency contribute to cardiovascular events and deaths in patients with CKD (24)(25)(26). Use of calcitriol in patients with stages 3-4 CKD is associated with improved survival; paricalcitol was shown in blinded trials to reduce proteinuria, but failed to alter left ventricular remodeling (27)(28)(29). However, proteinuria and left ventricular remodeling are intermediate outcomes, and no randomized trials have assessed mortality during use of VDRAs.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of observational and preclinical data, hypotheses have been generated that hyperphosphatemia, hypercalcemia, and calcitriol deficiency contribute to cardiovascular events and deaths in patients with CKD (24)(25)(26). Use of calcitriol in patients with stages 3-4 CKD is associated with improved survival; paricalcitol was shown in blinded trials to reduce proteinuria, but failed to alter left ventricular remodeling (27)(28)(29). However, proteinuria and left ventricular remodeling are intermediate outcomes, and no randomized trials have assessed mortality during use of VDRAs.…”
Section: Discussionmentioning
confidence: 99%
“…This novel finding provides a potential explanation for seemingly conflicting findings from previous studies. Calcitriol has been associated with improved survival among patients with CKD (28). However, calcitriol raises FGF23 levels (23), and elevated FGF23 is an independent risk factor for death (4).…”
Section: Discussionmentioning
confidence: 99%
“…3 Sesso et al and Fernandes et al showed that most patients who start on RRT in our country is referred to nephrology services very late, and most are on stage 4 (47.3%), which contrasts with data in international literature, in which most patients are on stage 3. [3][4][5][6][7][8][9][10][11][12][13][14][15] Besides the expected contribution of age and CKD staging, the correlation of proteinuria with the progression of the renal disease, even if eased by the renoprotection by ACEI and ARB, is demonstrated in many studies. [16][17][18] This phenomenon is clearly observed in patients with type II DM, in which ¼ of the patients presents with renal compromise after ten years of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these facts, it is interesting to observe the results are in accordance with prior studies, which clearly showed the important benefits of vitamin D for CKD. 8,26 In the beginning of the study, the observation that SAP and DAP were inadequate and were not associated to the outcomes represented by the need for RRT and death deserves some attention, even though it was not the only observation. The fact that pressure levels were higher than recommended in the base period of the study does not necessarily means that they stayed this way during follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation